2018
DOI: 10.2174/1872208311666171122152131
|View full text |Cite
|
Sign up to set email alerts
|

The Ecstacy of Gold: Patent Expirations for Trastuzumab, Bevacizumab, Rituximab, and Cetuximab

Abstract: This article will review these four notable monoclonal antibodies, their role in clinical oncology, and the drug patents that are nearing expiration. There are currently only two biosimilars approved in the United States: the trastuzumab biosimilar trastuzumab-dkst (Ogivri) and the bevacizumab biosimilar bevacizumab-awwb (Mvasi). In Europe, SB3, a trastuzumab biosimilar, is approved for use as well as two rituzimab biosimilars, truxima and rixathon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Similar disparities are also seen in LMICs in different parts of the world. In a RWD study from China, patients with early stage breast cancer in resource-abundant regions were more likely to receive trastuzumab than those in resource-limited regions (37% versus 13%, p < 0.05) [41]. Similarly, an observational study of Chinese patients with HER2+ tumours reported that 27% of those with advanced disease did not receive trastuzumab at any time after diagnosis and 49% did not receive trastuzumab in the first-line setting [14].…”
Section: Barriers To the Incorporation Of New Therapies For Advanced mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar disparities are also seen in LMICs in different parts of the world. In a RWD study from China, patients with early stage breast cancer in resource-abundant regions were more likely to receive trastuzumab than those in resource-limited regions (37% versus 13%, p < 0.05) [41]. Similarly, an observational study of Chinese patients with HER2+ tumours reported that 27% of those with advanced disease did not receive trastuzumab at any time after diagnosis and 49% did not receive trastuzumab in the first-line setting [14].…”
Section: Barriers To the Incorporation Of New Therapies For Advanced mentioning
confidence: 99%
“…Patents for several biologic drugs, including trastuzumab, have recently expired or will soon expire, which has stimulated the development of biosimilars [41]. Several countries have implemented abbreviated pathways for approval of biosimilars.…”
Section: Moving Forwardmentioning
confidence: 99%
“…17,24,29,30 Trastuzumab referans ürününün patentleri Avrupa Birliği (AB) ve ABD'de (sırasıyla 2014 ve 2019) kısa süre önce sona ermiştir. [31][32][33] Bunla birlikte alternatif olarak firmalar biyobenzer ilaç geliştirme çalışmalarını hızlandırmışlardır.34 Meme kanseri için insan epidermal büyüme faktörü reseptörü 2 (HER2) pozitifliği yüksek dereceli histoloji, lenf nodu tutulumu, daha yüksek hastalık nüksetmesi ve mortalite oranları ile ilişkisi nedeniyle kötü prognoz çerçevesi oluşturmaktadır.3 5 Meme kanserine karşı bir monoklonal antikor olan trastuzumab (Herceptin Roche / Genentech GmbH), bu hastalığın doğal seyrini değiştiren ve HER2 proteinini hedefleyen etkili bir ilaçtır. 5,35,36 Trastuzumab biyobenzerinin yanı sıra tedavide, tümör anjiyogenezini bloke edebilen bevacizumab(vasküler endotelyal büyüme faktörünü bağlayan bir monoklonal antikor -VEGF)da kulanılmaktadır.…”
Section: Biyobenzerlerin öNemiunclassified
“…In addition, monoclonal antibodies such as cetuximab and trastuzumab that target growth receptors overexpressed by cancer cells are used in both first and second line treatment regimens for common malignancies [ 7 ]. Despite the reported clinical benefits of targeted monoclonal antibodies, such as trastuzumab, and continued clinical use, the majority of patients develop therapeutic resistance that remains poorly understood [ 8 ].…”
Section: Introductionmentioning
confidence: 99%